Pedestrian-friendly traffic signal control using eclipse sumo - Akyol, Görkem; Silgu, Mehmet Ali; Celikoglu, Hilmi Berk; Silgu, Mehmet Ali (EasyChair, 2019)
The center of the Kadıköy area in Istanbul is extremely crowded due to overlap of the terminals for the subway and the marine transit lines. When the Kadıköy-Kartal subway’s terminal is added in the middle of the Kadıköy in 2013 without the analysis on crowd dynamics, vehicular and pedestrian traffic have become much more complicated to be efficiently managed. When the pedestrians have a crossing gap, most of them make the decision of crossing without considering the signal phase. Likewise, when it is a pedestrian clearance phase, there can be situations where all the pedestrians cannot cross the street because of high density and insufficient green time. We therefore propose an adaptive traffic control system considering the traffic flows of road vehicles and pedestrians with field data. We have utilized the Eclipse SUMO micro-simulator in conjunction with TraCI for modeling the case. Comparison of fixed time and adaptive signal controllers is provided. Simulations have shown that, reductions in the delay time for both vehicles and pedestrians are achieved by using adaptive signal controllers. © 2020 Elsevier B.V., All rights reserved.
International Conference on Simulation of Urban Mobility, SUMO 2019 -- Berlin -- 237389
Keywords: [No Keywords]